2014
DOI: 10.1063/1.4863852
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoelectrochemical activity of vertically aligned ZnO-coated TiO2 nanotubes

Abstract: Vertically aligned ZnO-TiO2 hetero-nanostructures constructed of anatase TiO2 nanotubes (NTs) and wurtzite ZnO coatings are fabricated by atomic layer deposition of ZnO coatings on electrochemical anodization formed TiO2 NTs, and their photoelectrochemical activities are studied through photoelectrochemical and electrochemical characterization. Compared with bare TiO2 NTs, the transient photocurrent increases to over 1.5-fold for the annealed ZnO-coated TiO2 NTs under visible illumination. The ZnO-coated TiO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
0
23
1
Order By: Relevance
“…8. Compared to the undoped TiO 2 , the flat-band potential of the ␣-Fe 2 O 3 /TN5ZO photoanode shifted negatively from −0.40 V to −0.49 V. The flat-band potential plays an important role in PEC performance [37][38][39]. When a photovoltaic component with a more negative flat-band potential was used as the photoelectrode a higher open-circuit voltage could be expected for better photocatalytic performance.…”
Section: Samplementioning
confidence: 97%
“…8. Compared to the undoped TiO 2 , the flat-band potential of the ␣-Fe 2 O 3 /TN5ZO photoanode shifted negatively from −0.40 V to −0.49 V. The flat-band potential plays an important role in PEC performance [37][38][39]. When a photovoltaic component with a more negative flat-band potential was used as the photoelectrode a higher open-circuit voltage could be expected for better photocatalytic performance.…”
Section: Samplementioning
confidence: 97%
“…Many efforts have been devoted to incorporate another material within the TiO 2 nanostructures (e.g., nanotube layers, mesoporous networks, nanorods, and nanofibers). Metal oxides nanostructures (e.g., composed of WO 3 , SnO 2 , CuO, NiO, Al 2 O 3 , In 2 O 3 , and ZnO) turn out to be very suitable to form p–n or n–n junctions at the interface with TiO 2 to alter the band structure. Out of these, zinc oxide (ZnO) offers high electron mobility for fast charge transport and low carrier recombination rate.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the differences in conductivity and carrier recombination, it is also worth mentioning that ZnO and TiO 2 have close band gap energies (3.37 and 3.0–3.2 eV, respectively) . Since both materials complement in properties, many works have coupled ZnO and TiO 2 to form a new heterostructure, TiO 2 /ZnO or in a reverse manner, ZnO/TiO 2 structures …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the major bottle necks such as limited absorption of the visible light and higher recombination of the photo-generated charges are addressed through several strategies including doping, 4 decoration with metal and semiconductor nano-particles 5 and composite formation using other semiconductor materials. 6,7 In recent times, graphene and its derivatives (reduced graphene oxide-rGO) are also being investigated for improving the photo-catalytic/photovoltaic properties by forming composite with TiO 2 . [8][9][10] It is reported that excellent electronic conductivity of this 2D material helps in the separation of photo-generated charges which, in turn, improves the catalytic activities.…”
Section: Introductionmentioning
confidence: 99%